Impact of Metformin Use and Diabetic Status During Adjuvant Fluoropyrimidine‐Oxaliplatin Chemotherapy on the Outcome of Patients with Resected Colon Cancer: A TOSCA Study Subanalysis. (3rd January 2019) - Vernieri, Claudio; Galli, Fabio; Ferrari, Laura; Marchetti, Paolo; Lonardi, Sara; Maiello, Evaristo; Iaffaioli, Rosario V.; Zampino, Maria G.; Zaniboni, Alberto; De Placido, Sabino; Banzi, Maria; Damiani, Azzurra; et al.
Abstract: Background: Type 2 diabetes mellitus (T2DM) is associated with increased risk of colon cancer (CC), whereas metformin use seems to be protective. However, the impact of metformin use on the risk of death or disease recurrence after radical surgery for CC remains uncertain. Materials and Methods: This is a substudy conducted in patients with high‐risk stage II or stage III CC randomized in the TOSCA trial, which compared 3 versus 6 months of fluoropyrimidine‐oxaliplatin adjuvant chemotherapy. Objective of the study was to investigate the impact of metformin exposure during adjuvant chemotherapy on overall survival (OS) and relapse‐free survival (RFS). We also evaluated the impact of T2DM or metformin dosage on clinical outcomes. Results: Out of 3, 759 patients enrolled in the TOSCA trial, 133 patients with diabetes (9.2%) and 1, 319 without diabetes (90.8%) were recruited in this study. After excluding 13 patients with diabetes without information on metformin exposure, 76 patients with T2DM (63.3%) were defined as metformin users and 44 (36.7%) as metformin nonusers. After a median follow‐up of 60.4 months, 26 (21.7%) patients relapsed and 16 (13.3%) died. Metformin use was neither associated with OS (adjusted hazard ratio [HR], 1.51; 95% confidence interval [CI], 0.48–4.77; p = .4781) nor with RFS (HR, 1.56; 95% CI, 0.69–3.54; p = .2881). Similarly, we found no association between T2DM or metformin dosage and OS or RFS. Conclusions: Metformin use and T2DM did not impact on OS or RFS in patients with resected CC treated with adjuvant fluoropyrimidine‐oxaliplatin chemotherapy. Larger studies and longer follow‐up are required to clarify the potential efficacy of metformin in improving the prognosis of patients with CC. Implications for Practice: The role of the antidiabetic drug metformin in colon cancer prevention and treatment is highly debated. While low‐dose metformin reduced the incidence of colorectal adenomas in two prospective studies, its effect in patients with already established colon cancer remains unclear. In this study, the potential impact of metformin on the survival of resected colon cancer patients who received adjuvant chemotherapy was investigated in the context of the TOSCA study. We did not find any association between metformin use or dosages and patient survival. Prospective studies are required to draw definitive conclusions about metformin impact on colon cancer recurrence and survival. Abstract : The antidiabetic compound metformin has emerged as a promising antineoplastic drug. Type 2 diabetes mellitus is associated with increased risk of colon cancer, against which metformin use seems to be protective. This article is a timely report on the association between metformin use and survival of diabetic patients with colon cancer.